Trophic relationships in a tropical estuary - Nordlie, Frank G. (1975)
This is an investigation of trophic interrelationship in the Tortuguero estuary on the Caribbean coast of Costa Rica. Basic physical and chemical features of the estuary are described, and a preliminary carbon budget is calculated for the estuarine ecosystem. Seasonal cycles in the estuarine watershed follow the rainfall pattern with two wet and two dry seasons per year. Planktonic primary production was found to be higher during dry seasons. However, the input of allochthonous materials by river flow is greater during wet seasons. The preliminary carbon budget indicates that estuarine respiration accounts for more organic material than is produced in the estuary during either the wet or dry seasons. During wet seasons there is an increase in the number of typically freshwater fish species, and an increase in the number of typically marine forms during dry seasons. The most striking seasonal difference in the estuarine community is in the presence, during dry seasons, of dense aggregations of tismiche composed principally of larval shrimp and larval fishes.